Numerical study of two side-by-side cylinders with unequal diameters at low Reynolds number - Gao, Y. Y. (2013)
Two-dimensional laminar flow about two side-by-side unequal cylinders with different diameter ratios d/D and centre-to-centre spacing ratios T/D at Re=300 (based on the larger cylinder diameter) was simulated using a CFD software. Comparisons of experimental and numerical results were made to elucidate the degree of interference due to d/D and T/D and their effects on the flow patterns and vortex shedding frequencies. The findings showed that the flow patterns behind two unequal cylinders were distinctly different from that behind two equal side-by-side cylinders, with distinct in-phase and anti-phase vortex shedding, and random switching of modes of vortex shedding.